2015
DOI: 10.1186/s12894-015-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Benign prostatic hyperplasia complicated with T1DM can be alleviated by treadmill exercise—evidences revealed by the rat model

Abstract: BackgroundBoth benign prostatic hyperplasia (BPH) and Type-1 diabetes mellitus (T1DM) share similar epidemiologic features and are all associated with the insulin-like growth factor (IGF)-mediated hormonal imbalance. The purpose of this study is to understand whether exercise (EX) could alleviate DM and DM + BPH.MethodsSprague-Dawley rats were divided into eight groups: normal control, EX, BPH, BPH + EX, DM, DM + EX, BPH + DM, and BPH + DM + EX. T1DM was induced by intraperitoneal (ip) injection of streptozoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…GSEA results showed that terms enriched for GO and KEGG were mainly associated with the regulation of endopeptidases and peptidases and complement and coagulation. GSVA showed that enriched GO and KEGG terms were mainly associated with cellular responses to insulin-like growth factor stimulation and autophagy, which is consistent with previous studies that have shown that BPH is associated with insulin-like growth factor-mediated hormone imbalance [ 77 ] and impaired autophagy [ 78 ].…”
Section: Discussionsupporting
confidence: 89%
“…GSEA results showed that terms enriched for GO and KEGG were mainly associated with the regulation of endopeptidases and peptidases and complement and coagulation. GSVA showed that enriched GO and KEGG terms were mainly associated with cellular responses to insulin-like growth factor stimulation and autophagy, which is consistent with previous studies that have shown that BPH is associated with insulin-like growth factor-mediated hormone imbalance [ 77 ] and impaired autophagy [ 78 ].…”
Section: Discussionsupporting
confidence: 89%
“…Impact of T1DM on the prostate. A number of studies report that induction of diabetes caused a significant reduction in serum testosterone levels and in prostatic weight in rats (19,54). The lobe response to diabetes varied (92).…”
Section: T1dm and Ucodmentioning
confidence: 99%
“…To further explore steroid hormonesinduced genomic differences in mice, we used GSEA and GSVA. GSEA results showed that terms enriched for GO and KEGG were mainly associated with the regulation of endopeptidases and peptidases and complement and coagulation GSVA showed that enriched GO and KEGG terms were mainly associated with cellular responses to insulin-like growth factor stimulation and autophagy, as previous studies have shown that BPH is associated with insulin-like growth factor-mediated hormone imbalance 53 and impaired autophagy 54 .…”
Section: Discussionmentioning
confidence: 66%